Reuse potential of ablution water from IIUM masjid - Al-Mamun, Abdullah; Muyibi, Suleyman Aremu; Abdul Razak, Nur Asilah (2013)
A significant amount of water is required daily for IIUM Masjid, which can accommodate at least about 9000 people during the special prayer times. Unfortunately, the water used for ablution is discharged directly to the drain without any plan to recycle and reuse. Quantity and quality of the used water after ablution is determined in this study. Laboratory tests have indicated that, the used ablution water is not much polluted and can be easily recycled and reused for general cleaning and landscaping purpose, after sand filtration. On the other hand, treatment and reuse of commercial greywater would be too expensive in the contexts of Malaysian climate, where the rain-fed water is sufficiently available. It is realised that a low maintenance treatment system can be constructed to store, treat and reuse ablution water from the Masjid. The treated water can easily be used for the landscaping and toilet flushing activities, which will reduce the water consumption in the university.